A case study of emerging practice in speech-language therapy in a community practice context - Abrahams, Kristen (Department of Health and Rehabilitation Sciences, 2020)
Background: The profession of speech-language therapy (SLT) continues to struggle with challenges around equity and service delivery. The dominant medical model, characterised by one-on-one, individualised health care, is struggling to serve the large population in need of services. As such, there is a need to reconceptualise SLT practices toward a social justice focus. The study used clinical education as the entry point of exploration into how emerging professional practices (EPPs) may be developed. Aims/Objectives: The study aimed to describe and analyse a case study of an emerging professional practice in SLT as part of a university-school partnership in a peri-urban settlement in South Africa. The objectives were: 1. To describe and analyse the practice methods of the EPP, 2. To describe and analyse the educational and knowledge bases which support the EPP, and 3. To describe and analyse the underlying epistemology, ontology and methodology underpinnings shaping the EPP. Method: A qualitative case study methodology, guided by critical theory and decoloniality, was used. Final year SLT students were the primary participants for the study. Data were collected in the form of document analyses, participant observations, interviews, photovoice, and experiential drawings from a number of stakeholders (including SLT students, a school principal, a project coordinator, a library assistant and a clinical educator) from January to December 2017. The data were analysed using reflexive interpretation (Alvesson & Sköldberg, 2009) as a guiding frame. Findings: The three-level analysis process was used to generate the thesis offering. The first level of analysis was the construction of the overall case narrative - documenting the practice methods of the EPP through the experiences of the SLT students. The second level of analysis used thematic analysis approach to identify key themes emerging from the case narrative. Four key themes were explored in the form of narratives, collages and paintings. The third level of analysis used decoloniality (i.e. coloniality of power, knowledge and being) and the Relationship of Labouring Affinities (RoLA) as critical lenses to deepen my understanding of the case. Through using both RoLA and decoloniality, dialogue emerged as a critical form of engagement toward developing EPPs. The study specifically puts forward the concept of critical dialoguing as a necessary process for conscientisation and change. Conclusion: The findings of the study illuminated how SLT students navigated through their experiences of disruption of their traditional practice. The findings weave together participant narratives, drawings and collages to engage the reader in the EPP. The findings showed how critical engagement with political, historical, social and linguistic influences underlying their work in communication, facilitated new learning and insight into SLT practice. The thesis offering discusses the role of critical dialoguing in opening up space for critical discussions about the profession. In conclusion, supported disruption provided students with a platform to interrogate current SLT practices, re-examine the viability of practices to serve populations, and reflect on how the SLT profession can adapt and change with the changing needs of the population.